A multidisciplinary engineering summer school in an industrial setting - Larsen, Peter Gorm (2009)
Most university-level engineering studies produce technically skilled engineers. However, typically students face several difficulties whenworking in multidisciplinary teams when they initiate their industrial careers. In a globalised world, it becomes increasingly important that engineers are capable of collaborating across disciplinary boundaries and exhibit soft competencies, like communication, interpersonal and social skills, time planning, creativity, initiative, and reflection. To prepare a group of engineering and industrial design students to acquire those capabilities, an international summer school that combined industrial design with different kinds of engineering disciplineswas organised on the site of Bang&Olufsen (B&O) in Denmark. This multidisciplinary engineering summer school was attended by students from six European university-level teaching institutions and was supervised by teachers from those institutions and industrial experts from B&O. The main aim of the summer school was to allow students to work in teams, composed of students from different knowledge disciplines and with different cultural backgrounds, with the purpose of developing innovative concepts and products, within a strong industrial perspective.